Penatalaksanaan Fisioterapi pada Lansia dengan Kasus Gangguan Keseimbangan di Letjen Sutoyo RW 03 Lowokwaru - Nurlaili Hasanatul Aprilia; Sri Sunaringsih Ika Wardojo; Bonita Suharto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Letjen Sutoyo RW 03 Lowowaru is an urban area in Malang City. This area has a Health Center that plays a vital role in maintaining public health. The aging process is characterized by a decrease in the body's ability to adapt to external stress, which leads to a decrease in the physiological function of organs, systems, and overall body ability. One of the important functions of the body is to form balance, which refers to the ability to maintain the center of the body's position against the supporting base when standing, sitting, moving, or walking (Winter, 1995 in Howe, et al., 2008). This balance is essential to maintain stability when moving from one position to another (Lee & Scudds, 2003).